A new species of Oxyascaris Travassos, 1920 (Nematoda: Cosmocercoidea) parasite of Leptodeira annulata (Serpentes: Colubridae) from Brazil, with a key to the species of the genus - Ana Nunes Santos; Yuri Willkens; Luiz Fernando Neres Silva; Francisco Tiago de Vasconcelos Melo; Thayane Ferreira Fernandes (International Journal for Parasitology: Parasites and Wildlife, 2023)
During a helminthological survey of snakes in the Cerrado Biome in Maranhão State, Brazil, we found intestinal nematodes in Leptodeira annulata (Linnaeus), belonging to the genus Oxyascaris Travassos, 1920. We observed that the specimens found are distinct from their congeners by the combination of presented characters, mainly the cuticular expansion at the anterior region of the body, presence of a single papilla at the anterior cloacal lip, number, and arrangement of caudal papillae, presence of somatic papillae along body cuticle, as well as some morphometric characters. Thus, we describe the new species using light and scanning electron microscopy and, revise the morphological characters used to identify Oxyascaris spp. and propose a key to the species of the genus. Therefore, we describe the seventh species in the genus, the second reported to parasitize snakes, the sixth species recorded in Brazil, and the first described in the Cerrado Biome.